Pemodelan Sistem Multimedia Pembelajaran Konsep Bilangan Pecahan Pada Matematika Sekolah Dasar - sri siswanti (STMIK Sinar Nusantara, 2011)
Mathematics subjects need given to all students from primary schools to equip students with the ability to think logically, analytically, systematically, critically and creatively, as well as the ability to cooperate. Competence is needed so that learners can have the ability to acquire, manage, and utilize the information to survive in the ever-changing circumstances, uncertain, and competitive.Multimedia technology is one technology in the field of computers that have the ability to make media a more complete learning. Multimedia summarizes the various media in a container, thus facilitating the delivery of teaching materials and the user can engage in the learning process because the technology has the capability of multimedia interactive. This study aims to make system modeling of fractions concepts based multimedia technology for Primary Schools (SD) with UML (Unified Modeling Language) which is using use cases, state diagrams and diagrams activity. Results of the research is modeling system for the development of Multimedia Learning Fraction Concepts In Elementary School Key words : mathematics, multimedia, unified modeling language(UML)